An ergonomics prototype of adjustable chin stands aid for visual mechanical inspection at electronic manufacturing-based company in Kuantan, Malaysia - Nurainaa, Elias; Nafrizuan, Mat Yahya (IOP Publishing, 2018)
Chin stands aid is a device designed to reduce fatigue on the chin during the Visual Mechanical Inspection (VMI) task for operators in TT Electronic Sdn Bhd, Kuantan, Malaysia. It is also used to reduce cycle time and also improve employee well-being in terms of comfort. In this project, a 3D model of chin stands aid with an ergonomics approach is created using SOLIDWORKS software. Two different concepts were designed and the best one is chosen based on the Pugh concept selection method, concept screening and also concept scoring. After the selection of concepts is done, a prototype of chin stands aid will be developed and a simulation of the prototype is performed. The simulation has been executed by using Workbench ANSYS software as a tool. Stress analysis, deformation analysis, and fatigue analysis have been done to know the strength and lifespan of the product. The prototype also has been tested to know the functionality and also comfortability for the user to use the chin stands aid.